Single and choice reaction time during prolonged exercise in trained subjects: influence of carbohydrate availability - Collardeau, M.; Brisswalter, J.; Vercruyssen, F.; Audiffren, M.; Goubault, C. (European Journal of Applied Physiology, 2001)
The aim of the present study was to examine the effects of prolonged exercise at the ventilatory threshold and carbohydrate ingestion on single (SRT) and choice (CRT) reaction time. Eight well-trained triathletes completed three testing sessions within a 3-week period. Maximal oxygen uptake was determined in the first test, whereas the second and the third sessions were composed of a 100-min run (treadmill 15 min, overground 70 min, treadmill 15 min) performed at the velocity associated with the ventilatory threshold. During these submaximal tests, the subjects ingested (in random order) 8 ml·kg-1 body weight of either a placebo (Pl) or 5.5% carbohydrate (CHO) solution prior to the first submaximal run and 2 ml·kg-1 body weight every 15 min after that. The cognitive tasks were performed before and after exercise for CRT, and before, during each submaximal run and after exercise for SRT. Furthermore, at the end of each submaximal test subjects were asked to report their rating of perceived exertion (RPE). Results showed a significant positive effect of CHO ingestion on RPE and CRT performance at the end of exercise, while no effect of exercise duration was found in the Pl condition. After a 100-min run, during the CHO condition, CRT mean (SD) group values decreased from 688.5 (51) ms to 654 (63) ms, while during the Pl condition, RPE mean group values increased from 11 (2) to 16 (1.02) and CRT mean values remained stable [688 (104) ms vs 676 (73.4) ms, P>0.05]. No similar effect was observed for SRT. These results suggest that CHO-electrolyte ingestion during a100-min run results in an improvement in the complex cognitive performance measured at the end of that run.